Cellular census of human fibrosis defines functionally distinct stromal cell types and states - Thomas B. Layton; Lynn Williams; Fiona McCann; Mingjun Zhang; Marco Fritzsche; Huw Colin-York; Marisa Cabrita; Michael T. H. Ng; Marc Feldmann; Stephen N. Sansom; Dominic Furniss; Weilin Xie; et al. (Nature Communications, 2020)
New anti-fibrotics aided by a better understanding of fibrotic cell subsets and their functions are needed. Here the authors perform single-cell RNA-seq and CyTOF on nodules from patients with Dupuytren’s disease to map subsets and the state of mesenchymal cells during pathogenic fibrogenesis.